Prevalence of most commonly reported tobacco-associated lesions in central Gujarat: A hospital-based cross-sectional study - Manjiri Joshi; Mansi Tailor (Wolters Kluwer Medknow Publications, 2016)
Background: Oral cancer is a major health problem in tobacco users worldwide and is one of the ten most common cancers. India alone accounts for 1/3 rd of the world's oral cancer and has a high rate of potentially malignant disorders (PMDs). The most common predisposing factors are smoking, smokeless tobacco, betel nut in quid form (pan), alcohol, spicy food, and sharp broken tooth. There are various tobacco-associated lesions (TALs) which can be diagnosed at very early stage. This study was conducted to rule out association of smoking and smokeless tobacco with occurrence of TALs and its dose-response relationship. Materials and Methods: Total of 60,018 patients attending the Department of Oral Medicine and Radiology from January 2013 to December 2014 with different oral and dental symptoms were screened. Of these, 4795 patients satisfying inclusion and exclusion criteria formed the cohort of the present study. All the patients were informed regarding the study and an informed verbal consent was obtained, following which they were interviewed for tobacco-related habits and examined by the trained dental professionals for the presence of any lesion. Along with patients' demographic details, information regarding the type of habit, duration, and frequency was recorded. Statistical Analysis: Statistical analysis was performed using STATA 13.1 software (STATA 13.1 software by Stata Corp Ltd India Continent) by applying Pearson's Chi-square test with Fisher's exact test, Independent t-test, and ANOVA test. Results: The overall study population showed maximum cases having habit of smokeless tobacco (37.9%) and smoking tobacco (36.5%). The overall prevalence of TALs was found to be 7.98%. Our study found strong relation of duration and frequency of habit with respect to occurrence of the lesions. Conclusion: TALs are often subtle and asymptomatic. Therefore, it is important for the clinician to maintain a high index of suspicion, especially if risk factors such as tobacco habits are present.